2001
DOI: 10.1097/00007890-200107270-00014
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Tacrolimus Plus Mycophenolate Mofetil or Azathioprine Versus Cyclosporine Oral Solution (Modified) Plus Mycophenolate Mofetil After Cadaveric Kidney Transplantation: Results at 2 Years1

Abstract: All three immunosuppressive regi-mens provided excellent safety and efficacy. How-ever, the best results overall were achieved with tacrolimus+MMF. The combination may provide particular benefit to kidney allograft recipients who develop delayed graft function/acute tubular necrosis. Renal function at 2 years was better in the tacrolimus treatment groups compared with the CsA group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(64 citation statements)
references
References 18 publications
7
55
1
1
Order By: Relevance
“…However, the adverse event defined as an increase in serum creatinine levels seemed to be lower in the group of patients who received tacrolimus in combination with 2 g/d MMF (25.9%) than in patients who were treated with azathioprine (40.7%) or 1 g/d MMF (39%), although this difference did not reach statistical significance. Again, a multicenter trial that tested tacrolimus/MMF versus tacrolimus/azathioprine versus CsA-microemulsion/MMF, did not show statistical differences between the two tacrolimus-treated groups regarding renal function (17)(18)(19). However, both groups exhibited a better renal function in terms of serum creatinine than the group of patients who received CsA-microemulsion/MMF.…”
Section: Renal Functionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the adverse event defined as an increase in serum creatinine levels seemed to be lower in the group of patients who received tacrolimus in combination with 2 g/d MMF (25.9%) than in patients who were treated with azathioprine (40.7%) or 1 g/d MMF (39%), although this difference did not reach statistical significance. Again, a multicenter trial that tested tacrolimus/MMF versus tacrolimus/azathioprine versus CsA-microemulsion/MMF, did not show statistical differences between the two tacrolimus-treated groups regarding renal function (17)(18)(19). However, both groups exhibited a better renal function in terms of serum creatinine than the group of patients who received CsA-microemulsion/MMF.…”
Section: Renal Functionmentioning
confidence: 92%
“…Tacrolimus/MMF association has not offered apparent advantages on BP control in comparison with dual therapy or triple therapy with steroids/tacrolimus/azathioprine or steroids/CsA/MMF, although detailed data are not available in several studies (15)(16)(17)(18)(19). However, tacrolimus/MMF combination has been tested as a steroid-sparing strategy after kidney transplantation in selected low-risk patients.…”
Section: Arterial Hypertensionmentioning
confidence: 99%
“…Recently, the introduction of newer, more immunosuppressive MI Ω myocardial infarction CHF Ω congestive heart failure DVT Ω deep vein thrombosis PE Ω pulmonary embolism CMV Ω cytomegalovirus agents (tacrolimus, MMF, microemulsion cyclosporine, rapamycin) allows an overall reduction in early rejection episodes. With these agents in a noninduction regimen, some studies have reported a rejection rate of 15% or less (20,21,28). To this end we have shown that the coadministration of these newer immunosuppressive agents and the limited dosing (a single 5 mg intraoperative dose) of induction agents (e.g.…”
mentioning
confidence: 92%
“…At this juncture, it is worth contrasting the differences in renal function noted with the Rapa/MMF regimen by Larson et al (99) with that reported by Flechner et al (97) The CsA/MMF comparator in the study of Flechner et al could well have tilted their results toward inferior renal function as studies do suggest that the CsA/MMF combination may be associated with slightly inferior allograft function compared with the TAC/ MMF combination (101).…”
Section: Cni Avoidance With Rapa/mmf/prednisonementioning
confidence: 97%